O velho e o novo rural em Araras: análise do desenvolvimento rural a partir de uma categorização dos setores censitários - Farbelow, Marcus Vinícius (Universidade Federal de São Carlos, 2016)
The rapid and intense transformations that took place in the Brazilian countryside generated new configurations and productive arrangements, which, in different combinations and tensions with the so - called traditional formations, can be considered responsible for the complexity and heterogeneity prevailing in the contemporary rural landscape. In spite of the growing number of studies dedicated to the theme, there are very few that seek to analyze the diversity of compositions existing within the municipalities. The present work aims to contribute to the literature on rural development and rural settings by proposing to classify the rural sectors of the municipality of Araras, State of São Paulo, through the Demographic Census (2010), State of São Paulo, using criteria that allow them to capture their specificities (sectors for tourism, agricultural sectors, recreational farms, among others). In addition, this dissertation aims to present a Rural Development Index (IDR) for each category of the municipality in question, providing subsidies for the formulation and implementation of public policies. The methodology used was Group Analysis. The results obtained allow us to conclude that, even in a relatively small municipality, there are different rural realities, which demand different modes of interpretation and intervention. Considering that, this work has sought to generate not only the application of the same methodology in other areas of interest (municipalities, hydrographic basins, microregions, among others), but also to improve the techniques utilized and to carry out complementary studies, mainly off qualitative character, related to the multiple configurations of the rural world
The old and the new rural in Araras: analysis of rural development from a categorization of census tracts
Keywords: Desenvolvimento rural; Heterogeneidade; Categorização; Rural development; Heterogeneity; Categorization; CIENCIAS AGRARIAS